1992
DOI: 10.1177/00220345920710090601
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Plaque Formation and Gingivitis in Beagle Dogs by Topical Use of a Degradable Controlled-release System Containing Chlorhexidine

Abstract: The in vivo efficacy of a newly-developed dental application of a film-forming, chlorhexidine-containing system was examined in beagle dogs. A self-disintegrating film-forming solution was applied three times weekly to the dentitions of 7 out of 13 dogs, which were fed a soft-food diet. Plaque accumulation (Plaque Index) and gingival inflammation (Gingival Index) were recorded at one, two, four, six, and eight weeks. The local delivery of low-dose chlorhexidine to dogs significantly inhibited gingivitis and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…It is possible, moreover, that oral micro‐organisms may be exposed to sub‐inhibitory levels over time following the use of a topically sustained‐release delivery system or following the adsorption of inhibitor to oral tissues or dental material (Southard et al. 1984; Kozlovsky et al. 1992; Toumba and Curzon 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, moreover, that oral micro‐organisms may be exposed to sub‐inhibitory levels over time following the use of a topically sustained‐release delivery system or following the adsorption of inhibitor to oral tissues or dental material (Southard et al. 1984; Kozlovsky et al. 1992; Toumba and Curzon 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This creates a reservoir of CHX that results in a bacteriostatic milieu in the mouth 17,32‐34 . However, in vivo and in vitro studies show that plaque inhibition is achieved by the antibacterial effect of the chlorhexidine bound to the tooth surface rather than the chlorhexidine desorbed from other oral surfaces 18,34‐38 . The interaction of CHX with hydroxyapatite, enamel, root dentin, and soft oral tissues 39‐42 is the basis of its antibacterial and antiplaque efficacy in a natural tooth surface environment.…”
mentioning
confidence: 99%
“…Sanguinaria extract is incorporated in an oral rinse at a concentration of 0.03%, corresponding to 0.01% sanguinarine chloride. Therefore, it is possible that microorganisms in the mouth could be exposed to SC of antiseptics or fluorides over time following a regimen of rinsing or use of a topically sustained-release delivery sys tem [Kozlovsky et al, 1992;Toumba and Curzon, 1993]. In addition, it has been shown that chlorhexidine [Mandel, 1988;Addy et al, 1992] and sanguinarine [Southard et al.…”
Section: Discussionmentioning
confidence: 99%